Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/medicina59030457
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Antimicrobial Resistance in Gram-Negative and Gram-Positive Infective Endocarditis: A Multicentric Retrospective Analysis

Abstract: Background and Objectives: Multidrug-resistant microorganisms have made treating bacterial infections challenging. Resistance to antibiotics is expected to overcome efforts to produce new, effective antibacterial medication that is lifesaving in many situations. Infective endocarditis (IE) is a life-threatening infection that affects 5–15 per 100,000 patients annually and requires rapid antibiotic therapy to prevent morbidity and mortality. Materials and Methods: The present research assessed IE cases over fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…The plates were then incubated at a temperature of 37 C for 18-24 hours for bacteria [16] . Finally, measurements were taken every two days, and the diameter of the inhibition zones was measured in millimeters (mm) using Caliber after an overnight incubation [17] .…”
Section: Giving One Of the Following A Bacterial Suspension Inoculationmentioning
confidence: 99%
“…The plates were then incubated at a temperature of 37 C for 18-24 hours for bacteria [16] . Finally, measurements were taken every two days, and the diameter of the inhibition zones was measured in millimeters (mm) using Caliber after an overnight incubation [17] .…”
Section: Giving One Of the Following A Bacterial Suspension Inoculationmentioning
confidence: 99%
“…Consistent with the rapid increase in the burden of endocarditis, the frequency of antibiotic applications in endocarditis is also on the rising, leading to high levels of resistance to antibiotics are observed in global clinical practice [12]. A retrospective cohort study conducted in Romania from 2016 to 2021 with a multicentric database on endocarditis showed that among Gram-positive infections, Staphylococcus aureus was the most commonly involved pathogen, with a multidrug-resistant pattern in 11.2% of patients, while Acinetobacter baumannii had the highest resistance pattern of all Gram-negative pathogens, with 27.4% of all samples resistant to three or more antibiotics [12]. However, to date there has been no comprehensive study covering all regions to estimate bacterial AMR in endocarditis, which is insu cient to understand the global burden of AMR and to identify and target the highest priority pathogens in different regions.…”
Section: Introductionmentioning
confidence: 98%
“…The burden has been increasing annually, and substantial heterogeneity between regions [10,11], with most notable increases observed in high-income regions [10]. Consistent with the rapid increase in the burden of endocarditis, the frequency of antibiotic applications in endocarditis is also on the rising, leading to high levels of resistance to antibiotics are observed in global clinical practice [12]. A retrospective cohort study conducted in Romania from 2016 to 2021 with a multicentric database on endocarditis showed that among Gram-positive infections, Staphylococcus aureus was the most commonly involved pathogen, with a multidrug-resistant pattern in 11.2% of patients, while Acinetobacter baumannii had the highest resistance pattern of all Gram-negative pathogens, with 27.4% of all samples resistant to three or more antibiotics [12].…”
Section: Introductionmentioning
confidence: 98%
“…Numerous studies have documented the cardiopulmonary consequences of COVID-19 [ 11 , 12 , 13 ]. However, there is a relative shortage of research focusing on effective rehabilitation strategies.…”
Section: Introductionmentioning
confidence: 99%